Trismus in oral cancer patients undergoing surgery and radiotherapy - Padmanidhi Agarwal; H.R. Shiva Kumar; Kirthi Kumar Rai (Elsevier, 2016)
Objective: The aim of this study was to determine the incidence of trismus before and after surgery and subsequent radiotherapy for patients of oral cancer and to determine the risk factors for the same. Methods: 30 patients diagnosed with oral cancer were included. Maximum mouth opening was measured for each patient as the inter incisal distance and was measured on 4 occasions - preoperatively at the time of diagnosis, post-operatively at discharge from the hospital, post-radiotherapy and at 6 months follow-up. The site of cancer, staging and grading of the malignancy, the surgical treatment performed, method of reconstruction, details of radiotherapy and compliance to physiotherapy were recorded, to evaluate the risk factors for developing trismus. Results: Trismus was observed in 53.3% patients at the time of diagnosis which increased significantly post-surgery (86.7%) and post-radiotherapy (85.7%) and gradually decreased (65.4%) at 6 months. The use of flaps for reconstruction, delay in radiotherapy post-surgery and non-compliance of patients to physiotherapy were the risk factors for developing trismus, showing statistical significance (p < 0.05). Conclusion: Trismus is a significant complication of oral malignancies or its surgical and radiotherapy treatment, or both. Consideration must be given to its early diagnosis, to help in timely intervention and planning of preventive strategies.